O trabalho do profissional de nível médio de enfermagem nos novos dispositivos de atenção em saúde mental - Zerbetto, Sonia Regina; Pereira, Maria Alice Ornellas [UNESP] (Escola de Enfermagem de Ribeirão Preto / Universidade de São Paulo, 2005)
The study consists of a bibliographic survey covering mid-level nursing professionals in alternative mental health services, with the objective to reflecting on their work, considering the psychosocial model and its care intervention actions, based on the theoretical reference framework of the so-called light technologies. It was observed that there is a transition process from the traditional to the psychosocial model, from a technical model to the model of satisfying user needs and the importance of reviewing these professionals' training process, pointing out a new attitude of the nurse-teacher, who should aim for critical-reflective teaching that is aimed at the ideals of the Psychiatric Reform.

El estudio se trata de un inventario bibliográfico que abarca al profesional de enfermería de nivel medio en los servicios alternativos de salud mental, con objeto de reflexionar sobre su trabajo, teniéndose en cuenta el modelo psicosocial y sus acciones de intervención en la atención, basadas en el referencial teórico de tecnologías livianas. Se observa que hay un proceso de transición del método tradicional al psicosocial y del técnico a la satisfacción de las necesidades del usuario y la importancia de reconsiderar el proceso de formación de esta categoría profesional, resaltando una nueva postura del enfermero(a)-profesor(a) que busca una enseñanza crítica y reflexiva en dirección a los ideales de la Reforma Psiquiátrica.

O estudo consiste em levantamento bibliográfico abrangendo o profissional de nível médio de enfermagem nos serviços alternativos de saúde mental, com o objetivo de refletir sobre o seu trabalho, considerando o modelo psicossocial e as suas ações de intervenção na assistência, baseadas no referencial teórico de tecnologias leves. Observou-se que há um processo de transição do modelo tradicional ao psicossocial; do tecnicista à satisfação das necessidades do usuário e a importância de rever o processo de formação dessa categoria profissional, salientando a nova postura do enfermeiro-professor que deve buscar ensino crítico-reflexivo e direcionado para os ideais da Reforma Psiquiátrica.
The work of the mid-level nursing professional in the new mental health care services
El trabajo del profesional de enfermería de nivel medio y los nuevos servicios de atención en la salud mental
Keywords: psychiatric nursing; mental health; nursing care; enfermagem psiquiátrica; saúde mental; cuidados de enfermagem